The Experiential Pattern of Emotional Intelligence Displayed by International Students Studying for a Bachelor of Business Administration in Burapha University, Thailand - Suwannaset, Watunyoo (HRD Journal, 2013)
While recent reports reveal that the number of international students in Thailand has continuously increased over the past 7 years, the majority come from China and many have chosen to study the Bachelor of Business Administration program (BBA) provided by Burapha University. Studying overseas may entail difficulties for these students, experiencing new feelings arising from both an unfamiliar physical and learning environment, and a new culture. Emotional intelligence competencies (EQ-i) could be seen as essential skills for their adaptation. To investigate how the students might experience and exercise each emotional intelligence skill during their living and studying, a phenomenological qualitative research study was conducted with 10 students, 3 teachers and 2 staff. In this study, criterion sampling and the use of snowball techniques were employed to identify participants from Burapha University’s International College and Faculty of Management and Tourism. The semi-structured interview was the main data collection technique employed to discover these adjustment issues. The data were transcribed and categorized into themes. The main findings of this study were that most Chinese students adapted to their new learning environment by exercising emotional intelligence skills, particularly intrapersonal skills, adaptability skills and problem-focused coping strategies. Key words : International students, Chinese students, Emotional Intelligence, Experience pattern, Phenomenological study